1970
DOI: 10.1152/ajplegacy.1970.219.5.1359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ambient temperature on gastric secretion and food intake in the rat

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…More recent investigations have confirmed a reduction in gastric acid output following exposure to stress induced by a large variety of stimuli including restraint (4), rotation (5), high ambient temperature (6), unpredictable electrical shocks (7), endotoxin (8), or ionizing radiation (9). It has not, however, been apparent whether such an inhibitory response to stress is the consequence of a local mechanism or, as suggested more recently, has centrally mediated components involving the release of various neuropeptides (10)(11)(12).…”
mentioning
confidence: 97%
“…More recent investigations have confirmed a reduction in gastric acid output following exposure to stress induced by a large variety of stimuli including restraint (4), rotation (5), high ambient temperature (6), unpredictable electrical shocks (7), endotoxin (8), or ionizing radiation (9). It has not, however, been apparent whether such an inhibitory response to stress is the consequence of a local mechanism or, as suggested more recently, has centrally mediated components involving the release of various neuropeptides (10)(11)(12).…”
mentioning
confidence: 97%
“…A synergism occurs between restraint and exposure to cold (42). Cold restraint usually increases gastric acid secretion (45,46), which is mediated by the release of histamine in the stomach, and by histamine-2 (H 2 ) receptors under vagal influence (47). Cold restraint usually increases gastric acid secretion (45,46), which is mediated by the release of histamine in the stomach, and by histamine-2 (H 2 ) receptors under vagal influence (47).…”
Section: Gastric Hydrochloric Acid Secretionmentioning
confidence: 99%
“…The immunoreactivity is localized in nerve fibers and terminals, whereas TRH cell bodies are contained in the raphe nuclei (43, 74). The endogenous release of brain TRH in response to cold exposure (1) mimics the stimulatory effect induced by central injection of TRH (72,82,126). Recent studies demonstrated that intracerebroventricular injection of TRH antiserum significantly inhibited gastric acid secretion stimulated by pylorus ligation in rats (32).…”
Section: Physiological Rolementioning
confidence: 99%